Characteristics and Transport Properties of Oil Source Faults in Shixi Uplift, Junggar Basin - Kong, Decheng; Li, Jiachen (International Journal of Electric Power and Energy Studies, 2025)
Based on the comprehensive analysis of regional tectonic evolution and stratigraphic development characteristics , it is believed that a large number of strike-slip faults are developed in the Mosuowan Uplift and Shixi in the Junggar Basin. This study will reveal the relationship between the mechanism of oil-source fault transportation and oil and gas sealing and the accumulation of oil and gas outside the source through the analysis of the distribution characteristics and conductivity of oil-source faults in the Shixi Uplift. The Shixi Uplift developed two faults in the Hercynian and Early-Middle Yanshanian periods to the Permian, and partly to the bottom of the Triassic and Jurassic; the faulted strata in the Early Yanshanian period ranged from the Permian to the bottom of the Sangonghe River in the Jurassic, and partly cut downward into the Carboniferous; the faulted strata in the Middle Yanshanian period were mainly above the unconformity surface from the Jurassic to the bottom of the Cretaceous. The two- stage fault configuration relationship is good, providing good transportation conditions for oil and gas migration. At the same time, based on the analysis of fault ridges, mudstone smear factor (SSF) and fault mud ratio (SGR) , the fault drainage performance evaluation of the Shixi Uplift and the fault-sand combination control mechanism are established.